1989
DOI: 10.1159/000125234
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Regulation of Proopiomelanocortin Gene Expression in the Pituitary Gland of Hypothalamopituitary Intact and Hypothalamopituitary Disconnected Sheep

Abstract: Proopiomelanocortin (POMC) gene expression in the anterior pituitary (AP) gland has previously been shown to be positively regulated by CRF and AVP and negatively regulated by glucocorticoids. In the neurointermediate lobe () of the pituitary, however, POMC gene expression is under tonic inhibitory dopaminergic control. In the present study we have used hypothalamopituitary intact (HPI), ovariectomized (OVX), and OVX/hypothalamopituitary disconnected (OVX/HPD) ewes to examine direct (i.e. nonhypothalamic) effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

1990
1990
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 23 publications
1
6
1
Order By: Relevance
“…Indeed, the fact that we could not detect GR-immunoreactivity in the mouse or rat melanotrophs is in agreement with the majority of studies demonstrating the lack of GR (17)(18)(19)(20)(21), and the absence of glucocorticoid effect on either peptide secretion (22), POMC levels (23), or POMC gene expression (24)(25)(26)(27)(28) in the mammalian IL. Nevertheless some effects of glucocorticoids have been reported, but they did not lead to coherent conclusions.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, the fact that we could not detect GR-immunoreactivity in the mouse or rat melanotrophs is in agreement with the majority of studies demonstrating the lack of GR (17)(18)(19)(20)(21), and the absence of glucocorticoid effect on either peptide secretion (22), POMC levels (23), or POMC gene expression (24)(25)(26)(27)(28) in the mammalian IL. Nevertheless some effects of glucocorticoids have been reported, but they did not lead to coherent conclusions.…”
Section: Discussionsupporting
confidence: 90%
“…The fact that the sheep in experiment I were ovary intact, and those in exper iment 2 were ovariectomized, might be interpreted as possibly influencing ACTH secretory responses. There were, however, no differences in basal ACTH levels between experiments 1 and 2, and recent studies from this laboratory have shown that ovariectomy does not change anterior pituitary POMC mRNA levels in the sheep [26].…”
Section: Discussionmentioning
confidence: 60%
“…In a study of male sheep, testosterone decreased POMC mRNA levels in some, but not all, hypothalamic sites (Hileman et al 1996). In ewes, no difference in anterior pituitary POMC mRNA was reported between intact and GDX animals (Mercer et al 1989), while progesterone and oestradiol treatment appeared to increase anterior pituitary POMC mRNA (Whisnant et al 1992) in GDX ewes. Our present observations may be at odds with a number of studies which report higher ACTH content in the anterior pituitaries of female rats (Lesniewska et al 1990, Chisari et al 1995, though it is not clear if such differences reflect the species studied, or the methodology (mRNA vs peptide content) employed.…”
Section: Discussionmentioning
confidence: 78%
“…Total RNA was extracted from the hemipituitary glands as previously described (Mercer et al 1989) and 25 µg total RNA were run for Northern blotting. The RNA was hybridised with a 32 P-labelled ovine POMC probe (van der Pavert et al 1997).…”
Section: Anterior Pituitary Mrna Assaysmentioning
confidence: 99%